„Kulturní revitalizace“ v současném Baskicku - Martin Chochola (AntropoWebzin)
The article attemts to make an initial insight into the problematic of language and cultural revitalization process which has been carried out since 1975 to presence. The history of Basque country with a special stress on the circumsatncies of the origin of modern basque nationalism are briefly sketched in the paper. Political, economic and social trends of the period mentioned above are also described, the questions of language revitalization, bilingvism and political consequences are emphasized. The article is based on the fieldresearch which has been carried out in Gipuzkoa (Basque Autonomy) in the february-june period in 2009. The article aslo concerns Navarra and French-Basque regions.